Trained immunity: a cutting edge approach for designing novel vaccines against parasitic diseases? - Zhu, Jinhang; Liu, Jiaxi; Yan, Chao; Wang, Dahui; Pan, Wei (Frontiers in Immunology, 2023)
The preventive situation of parasitosis, a global public health burden especially for developing countries, is not looking that good. Similar to other infections, vaccines would be the best choice for preventing and controlling parasitic infection. However, ideal antigenic molecules for vaccine development have not been identified so far, resulting from the complicated life history and enormous genomes of the parasites. Furthermore, the suppression or down-regulation of anti-infectious immunity mediated by the parasites or their derived molecules can compromise the effect of parasitic vaccines. Comparing the early immune profiles of several parasites in the permissive and non-permissive hosts, a robust innate immune response is proposed to be a critical event to eliminate the parasites. Therefore, enhancing innate immunity may be essential for designing novel and effective parasitic vaccines. The newly emerging trained immunity (also termed innate immune memory) has been increasingly recognized to provide a novel perspective for vaccine development targeting innate immunity. This article reviews the current status of parasitic vaccines and antiinfectious immunity, as well as the conception, characteristics, and mechanisms of trained immunity and its research progress in Parasitology, highlighting the possible consideration of trained immunity in designing novel vaccines against parasitic diseases.